Optimization method to construct micro-anaerobic digesters networks for decentralized biowaste treatment in urban and peri-urban areas. (10th January 2020) - Thiriet, Pierre; Bioteau, Thierry; Tremier, Anne
Abstract: Innovative small scale treatments solutions are currently proposed to handle the growing need of biowaste valorization through a more circular economy. These new approaches are designed to be embedded in a decentralized treatment scheme which raises new challenges for the biowaste management at the territorial scale. This study, aimed at developing a method to design decentralized and micro-scale Anaerobic Digestion (mAD) networks in urban and peri-urban areas. A mixed integer linear program (MILP) was set up to identify the number of mAD, their sites and their capacities in order to minimize the payload-distances of biowaste and digestate transportation while taking into account the technical constraints of the system. A Geographic Information System (GIS) methodology was developed to feed the MILP model with very fine-scale data about (1) the location and the characterization of the biowaste sources and of the digestate outlets (agricultural areas), and (2) the location of the potential sites for mAD based on a multi-criteria analysis that includes environmental regulations, urban planning rules, site accessibility and heat outlets for valorization. The method was applied to the territory of The Grand Lyon Metropole (534 km 2 ) in France. Optimized mAD networks were identified through the MILP according to different scenarios tested. Graphical abstract: Image 107712 Highlights: Decentralized micro-AD treatments imply adaptations of the territorial biowaste management. The newly developed method with MILP and GIS allows spatially optimized micro-AD networks. The GIS analysis is adapted to provide high resolution data on comparatively large areas. The MILP integrates objectives and constraints parameters of the system with contextual GIS data. The MILP allows to easily test scenarios and to be applied on different geographical contexts.